Differential in Maximal Aerobic Capacity by Sex in Collegiate Endurance Athletes Consuming a Marginally Low Carbohydrate Diet. (4th July 2017) - Baranauskas, Marissa N.; Miller, Brian; Olson, Jordan T.; Boltz, Michelle; Richardson, Laura; Juravich, Matthew; Otterstetter, Ronald
ABSTRACT: Purpose : Although current sports nutrition recommendations advocate for a high carbohydrate (CHO) intake among endurance athletes, recent research has suggested that training with low CHO availability may augment adaptations to aerobic training. The purpose of this study was to observe the dietary habits of collegiate distance runners and to investigate the effects of habitual CHO intake on aerobic performance [VO2max (post)] during a competitive season.Methods : During an 8-week trial period, 12 ( N = 12) collegiate track athletes recorded their self-selected dietary intake via 24-hour recall. Analysis of CHO intake was conducted by a registered dietitian. Pre [VO2max (pre)] and post [VO2max (post)] season aerobic capacity assessments were performed using a one-way analysis of covariance (ANCOVA) with 2 covariates controlling for VO2max (pre) and CHO intake compared to the variance in VO2max (pre) and VO2max (post) by sex.Results : The average CHO was 4.11 ± 1.03 g/kg body mass (BM), with only one female athlete meeting dietary recommendations, consuming ≥ 6 g/kg BM. Male distance runners on average had a lower CHO than females. After adjusting for VO2max (pre) and CHO, there were statistically significant differences between VO2max (post) group means by sex with a difference of 12.62 ml/kg/min (95% confidence interval [CI], 2.12–23.12, p = 0.02), with CHO accounting for 18% of the variance in VO2max (post).Conclusion : Collegiate distance runners exhibited marked improvements in maximal aerobic capacity during the in-season while consuming a marginally low-CHO diet, with a predominant effect in males. Therefore, CHO intakes below current recommendations for endurance athletes might not be detrimental to aerobic training adaptations.